2009
DOI: 10.1259/bjr/54005160
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the extent of deep venous thrombosis and the extent of acute pulmonary embolism as assessed by CT angiography

Abstract: ABSTRACT. The aim of our study is to investigate prospectively the quantitative relationship between deep venous thrombosis (DVT) and acute pulmonary embolism (PE). 110 patients clinically suspected of having venous thromboembolic disease underwent combined CT pulmonary angiography (CTPA) and venography of lower limb veins. 44 patients presented with clinical signs of DVT and positive ultrasonography or ascending venography, but no clinical sign of PE (Group 1). 66 patients presented with clinical signs of PE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…12 There was also a significant relationship between risk of SVT and risk of DVT, as well as of PE, as others have recently reported. [13][14][15][16] Regarding sex differences, women were confirmed to have strongly and significantly higher rates of SVTs than men.…”
Section: Discussionsupporting
confidence: 52%
“…12 There was also a significant relationship between risk of SVT and risk of DVT, as well as of PE, as others have recently reported. [13][14][15][16] Regarding sex differences, women were confirmed to have strongly and significantly higher rates of SVTs than men.…”
Section: Discussionsupporting
confidence: 52%
“…9 Furthermore, the hypothesis that large pulmonary arteries are more likely to be obstructed by emboli originating from large veins was not confi rmed in a quantitative study using the PE clot load score on CTPA and the DVT clot load score on CTV. 10 However, in general, it should be noted that there is no correlation between the clinical severity of PE and the shape or distribution of intrapulmonary thrombus. In addition to the fi ndings of clinical imaging, clinical risk markers, such as the presence of shock, hypotension, right ventricular dysfunc- tion, and myocardial damage, should be considered when estimating the possibility of PE-related early mortality.…”
Section: Discussionmentioning
confidence: 99%
“…It could be speculated that different times between CT scans were responsible for these results. Similarly, a previous study showed that the extent of PE was positively associated with a higher probability of residual DVT 24 , although in another study, the clot burden of PE was not found to necessarily indicate that of DVT 25 .…”
Section: Discussionmentioning
confidence: 69%